The Influence of Second-hand Clothing Product Quality on Consumer Satisfaction at Mardika Market, Ambon City - Kaimudin, Umiyati; Rehatta, Geradin; Louhenapessy, William George M (Universitas Pattimura, 2025)
This study aims to analyze the impact of second-hand clothing quality on consumer satisfaction. Product quality was evaluated through performance, aesthetics, and durability indicators, assessed using questionnaires distributed to 50 respondents. The research employed a quantitative approach with simple linear regression analysis. The results indicated that second-hand clothing quality has a significant effect on consumer satisfaction, with a coefficient of determination of 30.3%. These findings suggest that consumers tend to be more satisfied when the quality of second-hand clothing meets or exceeds their expectations. This study emphasizes the importance of product quality in enhancing consumer satisfaction and provides recommendations for sellers to maintain quality standards and product transparency. The study also offers insights for businesses on sustainable marketing strategies in the second-hand clothing industry